A novel MADS‐box transcription factor PstMCM1‐1 is responsible for full virulence of Puccinia striiformis f. sp. tritici. (23rd February 2018) - Zhu, Xiaoguo; Jiao, Min; Guo, Jia; Liu, Peng; Tan, Chenglong; Yang, Qian; Zhang, Yang; Thomas Voegele, Ralf; Kang, Zhensheng; Guo, Jun
Summary: In many eukaryotes, transcription factor MCM1 gene plays crucial roles in regulating mating processes and pathogenesis by interacting with other co‐factors. However, little is known about the role of MCM1 in rust fungi. Here, we identified two MCM1 orthologs, PstMCM1‐1 and PstMCM1‐2, in the stripe rust pathogen Puccinia striiformis f. sp. tritici ( Pst ). Sequence analysis indicated that both PstMCM1‐1 and PstMCM1‐2 contain conserved MADS domains and that PstMCM1‐1 belongs to a group of SRF‐like proteins that are evolutionarily specific to rust fungi. Yeast two‐hybrid assays indicated that PstMCM1‐1 interacts with transcription factors PstSTE12 and PstbE1. PstMCM1‐1 was found to be highly induced during early infection stages in wheat and during pycniospore formation on the alternate host barberry ( Berberis shensiana ). PstMCM1‐1 could complement the lethal phenotype and mating defects in a mcm1 mutant of Saccharomyces cerevisiae . In addition, it partially complemented the defects in appressorium formation and plant infection in a Magnaporthe oryzae Momcm1 mutant. Knock down of PstMCM1‐1 resulted in a significant reduction of hyphal extension and haustorium formation and the virulence of Pst on wheat. Our results suggest that PstMCM1‐1 plays important roles in the regulation of mating and pathogenesis of Pst most likely by interacting with co‐factors.